2015
DOI: 10.1093/abbs/gmv009
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance of hippocampal H<sub>2</sub>S generation contributes to CUMS-induced depression-like behavior: involvement in endoplasmic reticulum stress of hippocampus

Abstract: The chronic unpredictable mild stress (CUMS) model is a widely used experimental model of depression. Exogenous stress-induced neuronal cell death in the hippocampus is closely associated with the pathogenesis of depression. Excessive and prolonged endoplasmic reticulum (ER) stress triggers cell death. Hydrogen sulfide (H2S), the third endogenous signaling gasotransmitter, plays an important role in brain functions as a neuromodulator and a neuroprotectant. We hypothesized that the disturbance of endogenous H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 64 publications
2
22
0
1
Order By: Relevance
“…We used the CUMS protocol to mimic the traits of depression, which were confirmed by the SPT, FST, TST, EPM, and OFT in mice in our behavioral studies. FLU is currently available on the market [35], and the present results are consistent with previous research [36]. e CUMS mouse model has been generally used to study the pathological mechanism of depressive disorder and screening antidepressant drugs [37].…”
Section: Discussionsupporting
confidence: 90%
“…We used the CUMS protocol to mimic the traits of depression, which were confirmed by the SPT, FST, TST, EPM, and OFT in mice in our behavioral studies. FLU is currently available on the market [35], and the present results are consistent with previous research [36]. e CUMS mouse model has been generally used to study the pathological mechanism of depressive disorder and screening antidepressant drugs [37].…”
Section: Discussionsupporting
confidence: 90%
“…A recent report has documented that the endogenous H 2 S level is decreased in chronic unpredictable mild stress (CUMS) [24]. In addition, our recent studies showed that H 2 S could prevent depressive-like actions in the behavioral models of depression [25,26].…”
Section: Introductionmentioning
confidence: 87%
“…In addition, recent report demonstrated that exogenous H 2 S alleviated the oxidative stress-induced rat hippocampal damage through its antioxidant effects [ 17 ]. Moreover, we have previously provided compelling evidence that CUMS induced the imbalance of proportion to endogenous H 2 S in hippocampus [ 18 ]. Thus, we speculated that H 2 S attenuates oxidative stress in hippocampus of CUMS-treated rats.…”
Section: Introductionmentioning
confidence: 99%